Arguments against routine administration of probiotics for NEC prevention. Issue 2 (April 2019) - Pell, Lisa G.; Loutet, Miranda G.; Roth, Daniel E.; Sherman, Philip M.
Abstract : Purpose of review: Necrotizing enterocolitis (NEC) is a leading cause of morbidity and mortality among premature neonates. Although randomized trials have shown that probiotics may be efficacious in the prevention of NEC, their use has not been universally adopted in the neonatal intensive care unit (NICU). Caveats regarding routine probiotic supplementation for the prevention of NEC are summarized in this review. Recent findings: Accumulating evidence indicates that prophylactic probiotic supplementation in preterm infants can reduce the incidence of NEC. However, substantial knowledge gaps, regulatory issues, and implementation challenges should be addressed before probiotics are introduced as standard of care for all preterm neonates. Limitations of published trial data have made it challenging to define regimens that optimize efficacy and safety in specific patient subgroups. Moreover, the current probiotic market lacks rigorous regulatory oversight, which could raise concerns about the quality and safety of probiotic products. Finally, implementation pitfalls include risks of cross-colonization and resource requirements to monitor and mitigate potential adverse events. Summary: Probiotics have shown promise in the prevention of NEC. However, there is insufficient evidence to guide the selection of optimal regimens. Furthermore, issues related to regulatory and institutional oversight should be addressed before supplementation is routinely implemented in NICUs.